2010
DOI: 10.1177/147323001003800311
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antiobesity Effects of an Amino Acid Mixture and Conjugated Linoleic Acid on Exercising Healthy Overweight Humans: A Randomized, Double-blind, Placebo-controlled Trial

Abstract: This single-centre, randomized, doubleblind, placebo-controlled trial investigated the effects of administering a mixture of four amino acids (lysine, proline, alanine and arginine) with or without conjugated linoleic acid to healthy overweight humans before and after exercising. Fortyone healthy subjects (body mass index ≥ 23 to < 30 kg/m 2 ) completed the study following randomization to receive either placebo or one of three test supplements: amino acid mixture 0.76 g/day; amino acid mixture 1.52 g/day; or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…It has been reported that a reduction of 1 cm in the WC corresponds to a reduction of 1 kg of visceral fat. Moreover, it has also been reported that, if WC is increased by 1 cm, the risk for the development of hypertension is increased by 2.49 times [42]. In the present study, the increased BMI and WC in HFD fed animals demonstrated the efficiency of HFD to induce obesity in these animals.…”
Section: Discussionsupporting
confidence: 74%
“…It has been reported that a reduction of 1 cm in the WC corresponds to a reduction of 1 kg of visceral fat. Moreover, it has also been reported that, if WC is increased by 1 cm, the risk for the development of hypertension is increased by 2.49 times [42]. In the present study, the increased BMI and WC in HFD fed animals demonstrated the efficiency of HFD to induce obesity in these animals.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, CLA did not affect the β-oxidation rate of fatty acids or induce significant alterations in the safety markers tested. MICHISHITA et al, 2010 [ 67 ] Forty-one healthy subjects Single-centre, randomized, double-blind, placebo-controlled trial Subjects were randomized to receive either placebo or one of three test supplements: amino acid mixture 0.76 g/day; amino acid mixture 1.52 g/day; or amino acid mixture 1.52 g/day coadministered with conjugated linoleic acid 1.6 g/day and exercises for a period of 12 weeks The results suggest that ingestion of these supplements might enhance the fat-burning effects of exercise. WANDERS et al, 2010 [ 68 ] Sixty-one healthy women and men Double-blind, placebo controlled study It was provided either by oleic acid, by industrial trans fatty acids or by a mixture of 80 % 9- cis , 11- trans and 20 % 10- trans , 12- cis CLA.…”
Section: Evidences From Human Studiesmentioning
confidence: 99%
“…The additive effects or synergistic impact of eating routines and exercise have recently been thoroughly studied. 4 , 5 Our research group has considered the impact of amino acid supplementation, in combination with exercise, on fat oxidation for over two decades. 6 15 Recently, we concentrated on the amino acids arginine, alanine, and phenylalanine, which are involved in glucagon synthesis and secretion when delivered acutely.…”
Section: Introductionmentioning
confidence: 99%